2015
DOI: 10.1002/jcb.25425
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mitochondrial Manganese Containing Superoxide Dismutase Protects Against Ochratoxin A‐Induced Nephrotoxicity

Abstract: Ochratoxin A (OTA) is a natural mycotoxin, involved in the development of important human and animal diseases. In this work we have studied the role of oxidative stress in the development of OTA nephrotoxicity and the effect of a new recombinant mitochondrial manganese containing superoxide dismutase (rMnSOD) to prevent kidney damage induced by OTA. Blood pressure, glomerular filtration rate and renal histology were analyzed in control rats and in OTA treated rats. In addition, lipid peroxidation, catalase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…However, the exact mechanism of OTA‐induced nephrotoxicity has not yet been completely understood. The results obtained in this study, in accordance with in vitro and in vivo studies (Abdel‐Wahhab, Aljawish, El‐Nekeety, Abdel‐Aziem, & Hassan, ; Ciarcia et al, ; Costa et al, ; Periasamy, Kalal, Krishnaswamy, & Viswanadha, ), confirmed that the toxic effect of OTA on the kidney found both on the functional level and from the histopathology of view is mediated by oxidative stress. It has been shown that OTA acts by inhibiting the nuclear factor, which would affect both the synthesis and the recycling of glutathione and also the activity of oxidoreductases thus making the tissue more vulnerable to oxidative stress (Jennings, Limonciel, Felice, & Leonard, ; Limonciel & Jennings, ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the exact mechanism of OTA‐induced nephrotoxicity has not yet been completely understood. The results obtained in this study, in accordance with in vitro and in vivo studies (Abdel‐Wahhab, Aljawish, El‐Nekeety, Abdel‐Aziem, & Hassan, ; Ciarcia et al, ; Costa et al, ; Periasamy, Kalal, Krishnaswamy, & Viswanadha, ), confirmed that the toxic effect of OTA on the kidney found both on the functional level and from the histopathology of view is mediated by oxidative stress. It has been shown that OTA acts by inhibiting the nuclear factor, which would affect both the synthesis and the recycling of glutathione and also the activity of oxidoreductases thus making the tissue more vulnerable to oxidative stress (Jennings, Limonciel, Felice, & Leonard, ; Limonciel & Jennings, ).…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown a significant increase of ROS levels and a severe reduction of antioxidant enzymes in OTA treated cells showing lesions in the cell membrane, proteins, and DNA [Baudrimont et al, 1997;Liu et al, 2012]. In accordance with these authors, we have shown, in an our previous paper, that three important parameters of oxidative stress, such as malondialdehyde, SOD and catalase were altered in the kidney of OTA treated rats [Ciarcia et al, 2016]. In the present study we have measured the O 2 À and NO production.…”
Section: Discussionsupporting
confidence: 88%
“…After 1 week‐adaptation, these rats were randomly enrolled into four groups, were treated for 14 days by gavage, as follows: Control group ( n = 6:rats received 1 ml of corn oil containing 10% DMSO; Delta group ( n = 6); rats treated with Delta (60 mg/ kg of body weight) dissolved in DMSO and later scaled to the required volume with corn oil; OTA group ( n = 6): rats treated with OTA (0.5 mg/kg of body weight) dissolved in 10% DMSO and then scaled to required volume with corn oil; OTA plus Delta group ( n = 6): rats treated with Delta (60 mg /kg of body weight) plus OTA (0.5 mg/kg kg of body weight). The doses and times of Delta and OTA administration were chosen according to previous experiments (Ciarcia et al, ; Rodzian, Aziz Ibrahim, Nur Azlina, & Nafeeza, ). The rats were weighed at baseline (before receiving the first dose), five, 10, and at the end of the 14 days treatment.…”
Section: Methodsmentioning
confidence: 99%